Comprehensive evaluation of growth characteristics, nitrogen removal capacity, and nutritional properties of three diet microalgae - Zhang, Lin; Han, Jichang; Ma, Shuonan; Zhang, Yuanbo; Wang, Yumeng; Xu, Jilin (Frontiers in Marine Science, 2023)
Nitrogen is one of the main pollution sources in aquaculture system. Microalgae are considered as one of the ideal bio-absorbents used in wastewater purification, due to their nitrogen removal capacity and more importantly nutritional value. Nannochloropsis oceanica, Cyclotella atomus, and Conticribra weissflogii are famous as diet microalgae. However, estimation of nitrogen removal capability and concomitant nutritional properties of the three species have been rarely reported, which was performed in this study. N. oceanica, C. atomus, and C. weissflogii were cultivated with two initial nitrate-N concentration, noted as NC (13.85 mg·L–1) and NW (5 mg·L–1) groups, respectively. All the three microalgal strains in NC group showed higher maximum cell density, specific growth rate, and biomass concentration, maximal quantum yield of PSII (Fv/Fm), total Chlorophyll and carotenoids contents than that in NW group. These results confirmed the importance of nitrogen for microalgal biomass generation and photosynthetic performance. From Fv/Fm, N. oceanica has better adaptability towards nitrogen depletion compared to other two selected strains. The three microalgae exhibited significantly stronger nitrate-N absorption efficiencies in NC group at the same timepoint, compared to NW. Analyzing the average amount of nitrate-N absorbed by each cell daily, C. weissflogii gained the largest value, followed successively by C. atomus and N. oceanica, likely due to species specificity. Moreover, three strains removed 90% of nitrate-N within five days and 99% of that within seven days, showing splendid nitrogen removal potentials. These results confirmed the feasibility of removing nitrogen from wastewater with the selected three microalgae. Nutritional properties of microalgal biomass were also investigated. For the three species, lower nitrate-N was beneficial for the production of soluble sugar, total lipid, and saturated fatty acid, while higher nitrate-N led to more soluble protein and polyunsaturated fatty acid. In summary, N. oceanica, C. atomus, and C. weissflogii all showed strong nitrogen removal capacity, whose growth characteristics and nutritional properties varied with nitrogen concentration. In practical application for assimilating nitrogen, these findings could provide some references for the selection of suitable microalgae species in order to satisfy different nutritional requirements of various aquatic animals.